Method for detecting content of carbides in high-carbon chromium bearing steel

The carbon content of high-carbon chromium bearing steel is measured by a high-frequency infrared carbon sulfur analyzer and the carbide content is calculated, which solves the problems of large detection errors and cumbersome operation in the prior art, and achieves efficient and accurate carbide content detection.

CN119666778APending Publication Date: 2025-03-21CHINA RAILWAY CONSTR HEAVY IND
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411773952.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The prior art has problems such as large errors, cumbersome operation and low results when detecting the carbide content in high-carbon chromium bearing steel, which is difficult to meet the rapid testing needs of industrial production.

Method used

The carbon content of high-carbon chromium bearing steel is measured by a high-frequency infrared carbon sulfur analyzer, and the carbide content is calculated using specific formulas, including the carbon content of martensite structure and the overall carbon content of high-carbon chromium bearing steel.

Benefits of technology

It realizes efficient and accurate detection of carbide content in high-carbon chromium bearing steel, with small errors and simple operation, and can meet the rapid detection needs of industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119666778A_ABST
    Figure CN119666778A_ABST
Patent Text Reader

Abstract

The invention provides a method for detecting the content of carbides in high-carbon chromium bearing steel, the content of the carbides is calculated according to a formula 1: omegac * 6.69% + (1-omegac) * CM = C0 (formula 1), omegac is the content of the carbides, CM is the carbon content of a martensitic structure in the high-carbon chromium bearing steel, and C0 is the carbon content of the high-carbon chromium bearing steel. The detection method provided by the invention can accurately measure the carbide content of the high-carbon chromium bearing steel after spheroidizing annealing treatment and quenching treatment, and the measurement process is efficient, simple and easy to operate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for detecting carbide content in high-carbon chromium bearing steel, and belongs to the field of metal processing. Background Art

[0002] High carbon chromium bearing steel is the most widely used type of bearing steel in my country. After proper heat treatment, it can meet the use requirements under general conditions. In industrial production, the content of retained austenite in high carbon chromium bearing steel is often used as an important detection index to determine whether the product performance meets the requirements. The current standard uses the "five-line six-pair method" to determine the content of retained austenite in high carbon chromium bearing steel. This method requires the content of carbides in high carbon chromium bearing steel to be known in advance.

[0003] At present, the main methods for detecting the carbide content in high-carbon chromium bearing steel are metallographic method and electrolytic extraction method. The metallographic method is to select a suitable corrosive agent through a series of steps such as sampling, sample preparation, corrosion, observation and measurement, so that the carbide and other tissues show different contrast, and observe and calculate the carbide content under a metallographic microscope or scanning electron microscope. The electrolytic extraction method is to use appropriate electrical parameters and electrolytes to dissolve other tissues in high-carbon chromium bearing steel, retaining only carbides that are insoluble in the electrolyte, collect the carbides in the high-carbon chromium bearing steel by filtration, and then calculate the carbide content in the high-carbon chromium bearing steel by weighing.

[0004] However, the disadvantage of the metallographic method is that carbide and austenite are difficult to distinguish under an optical microscope, the statistical difficulty is large, the error is large, and a large number of fields need to be statistically analyzed to obtain the average value. The electrolytic extraction method is cumbersome to operate, has a high dependence on process parameters and is limited to the pore size of the filter paper. The results are always low, the cycle is long, and it is difficult to obtain results in time, which does not meet the requirements of industrial testing.

[0005] Therefore, in order to accurately and effectively measure the content of retained austenite in high carbon chromium bearing steel and provide guidance for industrial production, an efficient and accurate means to detect the content of carbides in high carbon chromium bearing steel is urgently needed. Summary of the invention

[0006] The invention provides a method for detecting the carbide content in high-carbon chromium bearing steel. The method can accurately and efficiently detect the carbide content in the high-carbon chromium bearing steel and is simple to operate.

[0007] In one aspect, the present invention provides a method for detecting the carbide content in high carbon chromium bearing steel. The carbide content is calculated according to Formula 1:

[0008] ω c ×6.69%+(1-ω c )×C M =C0 Formula 1

[0009] Among them, ω c is the carbide content, C M is the carbon content of the martensitic structure in the high carbon chromium bearing steel, and C0 is the carbon content of the high carbon chromium bearing steel.

[0010] In the detection method described above, the high carbon chromium bearing steel includes one of GCr15, GCr15SiMn, GCr15SiMo, and GCr18Mo.

[0011] According to the detection method described above, the structure of the high carbon chromium bearing steel includes martensite structure, residual carbide and austenite structure.

[0012] In the detection method described above, the carbon content of the high carbon chromium bearing steel is tested using a high-frequency infrared carbon-sulfur analyzer.

[0013] As described above, when the detection method is tested using the high-frequency infrared carbon-sulfur analyzer, the sample mass for a single test is 0.4 g and the test time is 30-35 s.

[0014] According to the above detection method, the carbon content of the martensite structure is obtained according to Formula 2:

[0015] y=-749.25C M 4 +2697.8C M 2 +2647.2C M +141.56 Formula 2

[0016] Wherein, y is the hardness of the martensitic structure.

[0017] As described above, the hardness measurement process of the detection method includes the following steps: acid-treating the sample of the high carbon chromium bearing steel with a 4% nitric acid alcohol solution, and then measuring the sample with a microhardness tester under a load of 0.2-0.5kgf and a dwell time of 10-20s to obtain the hardness.

[0018] In the detection method as described above, the acid treatment time is 3-4 minutes.

[0019] In the detection method as described above, the load is 0.2 kgf and the dwell time is 15 s.

[0020] The present invention provides a method for detecting the carbide content in high carbon chromium bearing steel. According to a specific formula, the carbide content in the high carbon chromium bearing steel is calculated using the carbon content of the martensitic structure in the high carbon chromium bearing steel and the carbon content of the high carbon chromium bearing steel. The method has low measurement difficulty, high accuracy and simple operation procedures for the relevant parameters used, and can efficiently and accurately obtain the carbide content in the high carbon chromium bearing steel. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is the optical microstructure image of high carbon chromium bearing steel after quenching;

[0022] Figure 2 This is a curve relationship diagram of the hardness of high carbon chromium bearing steel, martensitic structure hardness and carbon content. DETAILED DESCRIPTION

[0023] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] The present invention provides a method for detecting the carbide content of high carbon chromium bearing steel. The carbide content is calculated according to Formula 1:

[0025] ω c ×6.69%+(1-ω c )×C M =C0 Formula 1

[0026] Among them, ω c is the carbide content, C M It is the carbon content of martensite (and retained austenite) in high carbon chromium bearing steel, and C0 is the carbon content of high carbon chromium bearing steel.

[0027] The detection method of the present invention is used to detect the carbide content in high-carbon chromium bearing steel, where the carbide content refers to the mass fraction of carbides in the high-carbon chromium bearing steel. The present invention can efficiently and accurately detect the carbide content.

[0028] The high carbon chromium bearing steel in the present invention refers to high carbon chromium bearing steel after spheroidizing annealing and quenching. The high carbon chromium bearing steel after spheroidizing annealing and quenching has high hardness and strength, is suitable for bearing applications under high load, high speed and complex working conditions, and has excellent performance and stability.

[0029] The present invention does not limit the specific parameters of the spheroidizing annealing treatment of high carbon chromium bearing steel, and appropriate spheroidizing annealing parameters can be selected according to actual needs. For example, the spheroidizing annealing temperature is 780-800° C. and the time is 2-6 hours.

[0030] The present invention does not limit the specific parameters for quenching the high carbon chromium bearing steel after spheroidizing annealing. The high carbon chromium bearing steel can be quenched according to actual needs. For example, the austenitizing temperature is selected according to the AC1 temperature of the high carbon chromium bearing steel. Specifically, the AC1 temperature is increased by 50-80°C, kept at this temperature for 30 minutes, and oil quenched at 40°C for 10 minutes.

[0031] The microstructure of high carbon chromium bearing steel after quenching includes martensite, retained austenite and carbide. Figure 1 This is the optical microstructure image of high carbon chromium bearing steel after quenching.

[0032] Among them, since the transformation speed of the martensite structure is extremely fast, it can be considered that the carbon content of the martensite structure is the same as the carbon content of the retained austenite structure.

[0033] The inventors used the relationship between the carbon content of each structure in the high-carbon chromium bearing steel and the overall carbon content of the high-carbon chromium bearing steel to obtain Formula 1 through formula conversion. Among them,

[0034] The carbide content of high carbon chromium bearing steel is calculated according to formula 1:

[0035] ω c ×6.69%+(1-ω c )×C M =C0 Formula 1

[0036] Among them, ω c is the carbide content, C M is the carbon content of the martensitic structure in high carbon chromium bearing steel, and C0 is the carbon content of high carbon chromium bearing steel.

[0037] It can be understood that when the carbide content in the high carbon chromium bearing steel is calculated using Formula 1, Formula 1 can be mathematically transformed to more intuitively calculate the carbide content. For example, ω c =(C0-C M ) / (6.69%-C M ).

[0038] The detection method of the present invention realizes efficient and accurate detection of the carbide content of high-carbon chromium bearing steel. The carbide content calculated by formula 1 has a small error with the actual value, and does not require a large amount of statistics, and is simple to operate.

[0039] Furthermore, in a specific embodiment of the present invention, the high carbon chromium bearing steel includes one of GCr15, GCr15SiMn, GCr15SiMo, and GCr18Mo.

[0040] After a large number of creative experiments, the inventors found that when the detection method provided by the present invention is used to detect the above-mentioned type of high-carbon chromium bearing steel, the error between the detected carbide content and the actual value is small, and the detection result is more accurate. The inventors analyzed that the alloying element content of the above-mentioned type of high-carbon chromium bearing steel is relatively low, which has little effect on the hardness of the martensitic structure, making the detection result more accurate.

[0041] Furthermore, in a specific embodiment of the present invention, the structure of the high carbon chromium bearing steel includes martensite structure, residual carbide and austenite structure.

[0042] After a certain heat treatment process, samples with a large amount of bainite and troostite structures are not within the scope of the present invention.

[0043] Among them, metallographic microscope analysis, scanning electron microscope and energy spectrum analysis, X-ray diffraction and other methods can be used to detect the component types in high carbon chromium bearing steel.

[0044] When the structure of the high carbon chromium bearing steel includes martensite structure, residual carbide and austenite structure, the carbide content in the high carbon chromium bearing steel can be calculated more accurately using Formula 1.

[0045] Furthermore, in a specific embodiment of the present invention, the carbon content of the high carbon chromium bearing steel is tested using a high frequency infrared carbon-sulfur analyzer.

[0046] In detail, the detection of carbon content of high carbon chromium bearing steel specifically includes the following steps:

[0047] Take 2-3g of iron filings from the high carbon chromium bearing steel, then wash the iron filings twice with anhydrous ethanol and bake them at 80°C for 30 minutes to obtain a high carbon chromium bearing steel sample; use a high-frequency infrared carbon-sulfur analyzer to test the carbon content in the sample, with a sample mass of 0.3-0.5g for each analysis, repeat at least 3 times, and take the average value as the carbon content C0 of the high carbon chromium bearing steel.

[0048] The present invention does not limit the specific method of collecting iron chips, and a commonly used method in the art, such as collecting chips with a drilling machine, can be selected.

[0049] It can be understood that when using a high-frequency infrared carbon-sulfur analyzer to test the carbon content in a sample, it is necessary to select appropriate test parameters.

[0050] In a specific embodiment, the crucible used to hold the sample before analysis should be dried at 1100°C for 4 hours to remove moisture, and then stored in a drying dish after cooling with the furnace, and then the instrument accuracy is verified and calibrated by a standard sample with a carbon content of 1.0%. During analysis, the oxygen pressure is 0.08MPa, the top blowing oxygen flow rate is 1.2-2L / min, the oxygen flow rate during high-frequency combustion is 3-4 to 4.5L / min, the oxygen purity is greater than or equal to 99.95%, and 1.5-2.0g of tungsten particles with a purity greater than 99.9% are selected as flux.

[0051] When testing the carbon content of high-carbon chromium bearing steel using the above-mentioned testing conditions, clean and remove impurities, dry the crucible, reduce the uncertainty and the influence of moisture on the measurement, analyze the oxygen purity and pressure flow, and add high-purity tungsten particles as a flux to ensure that the carbon in the steel is fully converted into CO2 to ensure accuracy.

[0052] The use of a high-frequency infrared carbon-sulfur analyzer to measure the carbon content of high-carbon chromium bearing steel is not only fast and accurate, but also suitable for the need for rapid detection of the carbon content of high-carbon chromium bearing steel in industrial production.

[0053] Furthermore, in a specific embodiment of the present invention, the sample mass for a single test is 0.4 g, and the analysis time is 30-35 s.

[0054] In detail, the analysis time is 30-35 s. For example, the analysis time includes but is not limited to 30 s, 31 s, 32 s, 33 s, 34 s, 35 s or a range consisting of any two of them.

[0055] When the parameters are within the above range, it can ensure that the analysis is completed in a shorter time, improve the analysis efficiency, and ensure that the instrument obtains sufficient signals during the measurement process, avoid the influence of external interference, and provide accuracy and stability of the measurement results.

[0056] Further, in a specific embodiment of the present invention, the carbon content of the martensite structure is obtained according to Formula 2: y = -749.25C M 4 +2697.8C M 2 +2647.2C M +141.56 Formula 2

[0057] Where y is the hardness of the martensitic structure.

[0058] Among them, the hardness of standard products with different carbon contents can be tested to obtain equation 2 by fitting.

[0059] Specifically, the present invention obtains Formula 2 by the following steps:

[0060] 1) A series of carbon steels with different carbon contents (thickness of 0.8-1 mm) are obtained, with carbon contents ranging from 0.05% to 0.8%. The steels with the carbon contents can be obtained by carburizing in atmospheres with different carbon potentials, and the carbon contents can be measured by an infrared carbon-sulfur analyzer.

[0061] 2) The above steel samples are completely austenitized (heated to 30-50°C above AC3 temperature) and kept warm for 30 minutes.

[0062] 3) Quench with -5°C ice brine and then immediately place in liquid nitrogen for 2 hours.

[0063] 4) After returning to room temperature, measure the hardness of steel with different carbon contents after quenching and plot it Figure 2 And using polynomial fitting, we get Equation 2.

[0064] Specifically, the hardness value of the martensitic structure of the high carbon chromium bearing steel sample to be tested is substituted into Formula 2 to calculate the carbon content of the martensitic structure.

[0065] The present invention does not limit the method for determining the hardness of the martensitic structure, and the hardness may be determined using a common method in the art.

[0066] It can be understood that, for the convenience of practical operation, a series of C M Substitute into equation 2 and calculate y so that the carbon content parameters of the martensitic structure can be quickly obtained using the hardness, as shown in Table 1.

[0067] Table 1

[0068]

[0069] The method of determining the carbon content in the martensitic structure by the hardness of the martensitic structure using Formula 2 is efficient and convenient, does not require complicated test operations and equipment, and has positive significance for obtaining the carbide content efficiently and accurately.

[0070] Furthermore, in a specific embodiment of the present invention, the hardness measurement process includes the following steps: acid-treating a sample of high carbon chromium bearing steel with a 4% nitric acid alcohol solution, and then measuring the sample using a microhardness tester under a load of 0.2-0.5 kgf and a dwell time of 10-20 s to obtain the hardness.

[0071] The 4% nitrate alcohol solution in the present invention refers to an alcohol solution containing 4% nitric acid by volume.

[0072] In detail, a high carbon chromium bearing steel sample was selected, and the sample was ground and polished to make the surface of the sample smooth and flat, and then it was immersed and corroded in a 4% nitric acid alcohol solution, so that at least one observation surface of the sample was immersed in the nitric acid alcohol solution to remove impurities and contaminants on the surface of the high carbon chromium bearing steel. Then, the hardness of the martensitic structure in the high carbon chromium bearing steel sample was measured using a microhardness tester. The load during the measurement process was 0.2-0.5kgf, and the dwell time was 10-20s.

[0073] The residence time is 10-20 s. For example, the residence time includes but is not limited to 10 s, 11 s, 12 s, 13 s, 14 s, 15 s, 16 s, 17 s, 18 s, 19 s, 20 s or a range consisting of any two of them.

[0074] The present invention does not limit the specific process steps of grinding and polishing, as long as the surface of the high carbon chromium bearing steel can be made smooth and flat.

[0075] It is understandable that in order to make the hardness test result more accurate, the same sample can be tested repeatedly with a microhardness tester to calculate the hardness average of the multiple tests, for example, five times of measurement and the hardness average of the five tests.

[0076] The above-mentioned steps can be used to accurately and efficiently obtain the hardness of the martensitic structure in the high carbon chromium bearing steel without destroying the material, which is of great significance for further obtaining the carbon content and carbide content of the martensitic structure.

[0077] Furthermore, in a specific embodiment of the present invention, the acid treatment time is 3-4 minutes.

[0078] In detail, the acid treatment time is 3-4 min. For example, the acid treatment time includes but is not limited to 3 min, 3.1 min, 3.2 min, 3.3 min, 3.4 min, 3.5 min, 3.6 min, 3.7 min, 3.8 min, 3.9 min, 4 min or a range consisting of any two of them.

[0079] When the acid treatment time is within the above range, it can effectively remove oxides and contaminants while ensuring that the sample surface will not be excessively damaged. It is easier to distinguish carbides from other tissues, facilitates the hardness measurement of martensite tissue, and can make the treatment effect more stable and repeatable, thereby improving the reliability and comparability of the test results.

[0080] Further, in a specific embodiment of the present invention, the load is 0.2 kgf and the residence time is 15 s.

[0081] When the load and dwell time are within the above range, the hardness obtained from the test is more accurate, which lays the foundation for the accuracy of the carbide content finally calculated.

[0082] The detection method provided by the present invention is described in detail below through specific examples.

[0083] The high carbon chromium bearing steel used in the present invention is produced from an electroslag remelting continuous casting steel billet of a domestic special steel plant, and is rolled and spheroidized annealed.

[0084] Example 1

[0085] In this embodiment, the steps for detecting the carbide content of GGr15 high carbon chromium bearing steel are as follows:

[0086] 1) Detect the carbon content C0 of GGr15 high carbon chromium bearing steel: Take 3g of iron filings from GGr15 high carbon chromium bearing steel, then wash the iron filings twice with anhydrous ethanol, and bake at 80℃ for 30min to obtain GGr15 high carbon chromium bearing steel samples; the crucible used to hold the sample is dried at 1100℃ for 4h to remove moisture, and then stored in a drying dish after cooling with the furnace, and then the accuracy of the high-frequency infrared carbon and sulfur analyzer is verified and calibrated by a standard sample with a carbon content of 1.0%. During the analysis, the oxygen pressure is 0.08MPa, the top blowing oxygen flow rate is 2L / min, the oxygen flow rate during high-frequency combustion is 4.5L / min, the oxygen purity is greater than or equal to 99.95%, and 2.0g of tungsten particles with a purity greater than 99.9% are selected as flux. The sample mass of a single test is 0.4 g, the analysis time is 30 s, and it is repeated at least 3 times. The average value is the carbon content C0 of GGr15 high carbon chromium bearing steel, which is 1.02%.

[0087] 2) Detect the carbon content of the martensitic structure of GGr15 high carbon chromium bearing steel: heat treat the GGr15 high carbon chromium bearing steel sample after spheroidizing annealing, the sample size is 40*20*15mm, the heat treatment process is to use a resistance heating furnace to heat to 840°C, keep warm for 30 minutes and then cool in quenching oil, then use wire cutting to sample, grind and polish the sample to make the sample surface smooth and flat, then use 4% nitric acid alcohol solution for immersion corrosion, so that at least one observation surface of the sample is immersed in the nitric acid alcohol solution, the acid treatment time is 3 minutes, remove impurities and contaminants on the sample surface, and then use a microhardness tester to measure the hardness of the martensitic structure in the GGr15 high carbon chromium bearing steel sample, the load of the measurement process is 0.2kgf, and the dwell time is 15s;

[0088] The hardness of the martensitic structure obtained by the test is 842HV. It is substituted into Formula 2 to calculate the carbon content C of the martensitic structure in GGr15 high carbon chromium bearing steel. M It is 0.53%.

[0089] 3) The carbon content of high carbon chromium bearing steel C0 and the carbon content of martensite structure C M Substitute into formula 1 to calculate the carbide content ω of the high carbon chromium bearing steel c It is 7.95%.

[0090] Example 2

[0091] The detection method of the high carbon chromium bearing steel in this embodiment is basically the same as that in Embodiment 1, except that the high carbon chromium bearing steel in this embodiment is Gcr18Mo, and the heat treatment process is different.

[0092] The carbon content of the high carbon chromium bearing steel calculated by the above test is 0.99%. The heat treatment process is to heat it to 850°C in a resistance heating furnace, keep it warm for 20 minutes and then cool it in quenching oil. The carbon content CM of the martensitic structure is put into formula 1, and the carbide content ωc of the high carbon chromium bearing steel is calculated to be 8.21%.

[0093] Example 3

[0094] The detection method of the high carbon chromium bearing steel in this embodiment is basically the same as that in Embodiment 2. The high carbon chromium bearing steel in this embodiment is also Gcr18Mo, but the heat treatment process is different.

[0095] The carbon content of the high carbon chromium bearing steel calculated by the above test is 0.99%. The heat treatment process is to use a resistance heating furnace to heat to 880°C, keep it warm for 30 minutes and then cool it in quenching oil. The carbon content CM of the martensitic structure is substituted into Formula 1, and the carbide content ωc of the high carbon chromium bearing steel is calculated to be 6.86%.

[0096] Test example

[0097] The carbide contents of the high carbon chromium bearing steels in Examples 1-3 were tested in turn by conventional metallographic methods and electrolytic extraction weighing.

[0098] The samples after heat treatment in Example 1 were sampled and first detected by metallographic method: 4% nitric acid alcohol was used for corrosion, and 20 photos were taken at 1000 times using a metallographic microscope. After image processing and identification, the carbide contents (converted to mass fraction) were 9.46%, 9.25%, 7.76%, 8.37%, 8.05%, 10.82%, 6.91%, 8.34%, 8.93%, 10.14%, 8.57%, 8.93%, 7.62%, 8.03%, 8.44%, 8.36%, 8.61%, 8.73%, 8.05%, and 8.61%, respectively. The average value was taken, and the carbide content of the high carbon chromium bearing steel in Example 1 was measured to be 8.60%, and the error between the method provided in Example 1 and the metallographic method was 8.17%.

[0099] Then, the electrolytic extraction and weighing were used for testing: the sample after heat treatment was weighed to 0.2418g as the anode, 50g / L potassium chloride and 10g / L citric acid water were selected as the electrolyte, and the current density was 0.025-0.030A / cm 2 The electrolyte temperature is 0-5°C, filtered after electrolysis, and weighed to be 0.0184g, then the carbide content is 0.0184 / 0.2418=7.61%. The error between the method provided in Example 1 and the electrolytic extraction weighing method is 4.27%.

[0100] The samples after heat treatment in Example 2 were sampled and first detected by metallographic method: 4% nitric acid alcohol was used for corrosion, and 20 photos were taken at 1000 times using a metallographic microscope. After image processing and identification, the carbide contents (converted to mass fraction) were 8.99%, 8.82%, 8.31%, 9.09%, 9.14%, 7.61%, 8.55%, 8.31%, 8.50%, 8.10%, 9.11%, 8.86%, 7.47%, 7.81%, 8.19%, 8.32%, 8.21%, 8.45%, 9.22%, and 8.21%, respectively. The average value was taken, and the carbide content of the high carbon chromium bearing steel in Example 2 was measured to be 8.46%, and the error between the method provided in Example 2 and the metallographic method was 3.05%.

[0101] Then, the electrolytic extraction and weighing were used for testing: 0.2495 g of the sample after heat treatment was taken as the anode, 50 g / L potassium chloride and 10 g / L citric acid water were selected as the electrolyte, and the current density was 0.025-0.030 A / cm 2 The electrolyte temperature is 0-5°C, filtered after electrolysis, and weighed to be 0.0195g, then the carbide content is 0.0195 / 0.2495=7.82%. The error between the method provided in Example 1 and the electrolytic extraction weighing method is 4.75%.

[0102] The samples after heat treatment in Example 3 were sampled and first detected by metallographic method: 4% nitric acid alcohol was used for corrosion, and 20 photos were taken at 1000 times using a metallographic microscope. After image processing and identification, the carbide contents (converted to mass fraction) were 5.45%, 5.77%, 4.75%, 6.01%, 5.97%, 6.79%, 6.82%, 7.48%, 6.21%, 5.97%, 5.49%, 6.75%, 6.64%, 6.19%, 6.49%, 5.88%, 7.11%, 6.32%, 5.93%, and 6.09%, respectively. The average value was taken, and the carbide content of the high carbon chromium bearing steel in Example 3 was measured to be 6.21%, and the error between the method provided in Example 2 and the metallographic method was 9.48%.

[0103] Then, the electrolytic extraction and weighing were used for testing: 0.2533 g of the sample after heat treatment was taken as the anode, 50 g / L potassium chloride and 10 g / L citric acid water were selected as the electrolyte, and the current density was 0.025-0.030 A / cm 2 The electrolyte temperature is 0-5°C, and the electrolyte is filtered after electrolysis and weighed to be 0.0163g. The carbide content is 0.0163 / 0.2533=6.44%. The error between the method provided in Example 3 and the electrolytic extraction weighing method is 6.12%.

[0104] It can be seen that the method provided by the present invention has higher accuracy.

[0105] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for detecting carbide content in high carbon chromium bearing steel, characterized in that: The carbide content is calculated according to Formula 1: ω c ×6.69%+(1 - ω c )×C M = C0 Equation 1 Among them, ω c is the carbide content, C M is the carbon content of the martensitic structure in the high carbon chromium bearing steel, and C0 is the carbon content of the high carbon chromium bearing steel.

2. The detection method according to claim 1, characterized in that: The high carbon chromium bearing steel includes one of GCr15, GCr15SiMn, GCr15SiMo and GCr18Mo.

3. The detection method according to claim 1 or 2, characterized in that: The structure of the high carbon chromium bearing steel includes martensite structure, residual carbide and austenite structure.

4. The detection method according to any one of claims 1 to 3, characterized in that: The carbon content of the high carbon chromium bearing steel is tested by a high frequency infrared carbon-sulfur analyzer.

5. The detection method according to claim 4, characterized in that: When the high-frequency infrared carbon-sulfur analyzer is used for testing, the sample mass for a single test is 0.4 g and the testing time is 30-35 s.

6. The detection method according to any one of claims 1 to 5, characterized in that: The carbon content of the martensite structure is obtained according to Formula 2: y=-749.25C M 4 +2697.8C M 2 +2647.2C M +141.56 Formula 2 Wherein, y is the hardness of the martensitic structure.

7. The detection method according to claim 6, characterized in that: The hardness measurement process includes the following steps: acid-treating the sample of the high carbon chromium bearing steel with a 4% nitric acid alcohol solution, and then measuring the sample with a microhardness tester under a load of 0.2-0.5 kgf and a dwell time of 10-20 s to obtain the hardness.

8. The detection method according to claim 7, characterized in that: The acid treatment time is 3-4 minutes.

9. The detection method according to claim 7 or 8, characterized in that: The load is 0.2 kgf, and the dwell time is 15 s.

Citation Information

Patent Citations

  • Preparation method of retained austenite standard sample of high-carbon chromium bearing steel

    CN104215489A

  • Bloom GCr15SiMn bearing steel and smelting method thereof

    CN115007821A